Taiwan : nation-state or province? - Copper, John Franklin (Westview Press, 2009)
From the Publisher: In this newly revised and updated edition of Taiwan: Nation-State or Province?, author John Copper examines Taiwan's geography and history, society and culture, economy, political system, and foreign and security policies in the context of its uncertain political status: whether a sovereign nation or a province of the People's Republic of China. Copper argues that Taiwan's rapid and successful democratization suggests that it should be independent and separate from China, while increasingly important economic links between Taiwan and China indicate the opposite. New to the fifth edition is enhanced coverage of the issues of an aging population, immigration, Taiwan's loss of diplomatic status, and its improving commercial-though not political-relations with China. The new edition also examines the implications of the Chen Shui-bian administration and the 2008 presidential election.